THE CORRELATION BETWEEN STUDENTS' VOCABULARY MASTERY AND SPEAKING ABILITY AT A PRIVATE SCHOOL IN JAMBI - Farhana, Alifa; Ridha, Ahmad; Hidayati, Hidayati (JELT (Jambi-English Language Teaching), 2025)
This research aimed to determine the correlation between students’ vocabulary mastery and speaking ability of grade 9 of SMP Muhammadiyah 1 Kota Jambi. This research was quantitative research which used correlational technique design. The research sample was 40 students in grade nine, and total sampling was used. The instruments used in the study were a vocabulary test and a speaking test. The vocabulary test consisted of 20 questions in the form of 10 multiple choices, 5 matches up, and 5 fill blank and a speaking test in the form of describing something for 3-5 minutes. The correlation was measured through Pearson Product Moment. The results showed a strong relationship between vocabulary mastery and students' speaking ability, meaning that students' vocabulary mastery increased in line with students' speaking ability. It can be concluded that students' vocabulary mastery and speaking ability are good, and the correlation between students' vocabulary mastery and speaking ability is at a very strong level.